Determinants of the Level of Sharia Financial Literacy among Muslimah in Jabodetabek - Rosalina Saleh; Indra Indra; Nurul Hilmiyah (Syntax Corporation Indonesia, 2023)
As being known, financial literacy by definition, is knowledge, skills, and beliefs in which in many references influence attitudes and behavior of an individual to improve the quality of decision-making and financial management in order to achieve welfare. In Islamic financial literacy, welfare is falah. This study aims to determine the determinants of Islamic financial literacy levels in 391 productive age Muslim women in Jabodetabek. Methods of data analysis in this research using purposive sampling method and using SEM-PLS analysis. The results showed that of the four variables studied, the financial knowledge variable had no significant influence on Islamic financial literacy. While three other variables (financial attitude, financial behavior and religiosity) show significant influence to Islamic financial literacy.